2011
DOI: 10.1016/j.jchemneu.2011.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analyses of laser-captured hippocampus reveal distinct gray and white matter signatures associated with incipient Alzheimer's disease

Abstract: Alzheimer’s disease (AD) is a devastating neurodegenerative disorder that threatens to reach epidemic proportions as our population ages. Although much research has examined molecular pathways associated with AD, relatively few such studies have focused on the disease’s critical early stages. In a prior microarray study we correlated gene expression in hippocampus with degree of Alzheimer’s disease and found close associations between upregulation of apparent glial transcription factor/epigenetic/tumor suppres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
158
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(167 citation statements)
references
References 80 publications
9
158
0
Order By: Relevance
“…The overlap was statistically significant with p-values 2.20e-16 and 4.95e-5 for the up-and down-regulated genes, respectively. Another work by Blalock et al identified 277 up-and 232 down-regulated genes [15], among which 8 and 6 were in our list of up-and down-regulated genes. The overlap was also statistically significant with p-values 6.10e-8 and 2.97e-7 for the up-and down-regulated genes, respectively.…”
Section: Validation Of the 100 Genes In Independent Datasets For Admentioning
confidence: 70%
See 1 more Smart Citation
“…The overlap was statistically significant with p-values 2.20e-16 and 4.95e-5 for the up-and down-regulated genes, respectively. Another work by Blalock et al identified 277 up-and 232 down-regulated genes [15], among which 8 and 6 were in our list of up-and down-regulated genes. The overlap was also statistically significant with p-values 6.10e-8 and 2.97e-7 for the up-and down-regulated genes, respectively.…”
Section: Validation Of the 100 Genes In Independent Datasets For Admentioning
confidence: 70%
“…This LOAD dataset included 17 AD cases and 16 controls. In another study, Blalock et al conducted a microarray analysis on the gray matter of hippocampus CA1 region using laser capture microdissection [15]. Although the same 30 subjects were included as in their earlier work [16], different tissue selection techniques were used (tissue with mixed gray and white matters in their earlier work).…”
Section: Datasets and Data Processingmentioning
confidence: 99%
“…Additionally, we found that the expression of RBMS1 and/ or RBMS2 are significantly altered in a variety of human neurological diseases including the neurodegenerative disorders Alzheimer disease, Parkinson disease, X-linked dystonia-parkinsonism, and the mental disorder schizophrenia (Table S2; Blalock et al 2011;Blalock et al 2004;Harris et al 2008;Lesnick et al 2007;Lewandowski et al 2010). Collectively, the data suggest that RBMS1/2/3 orthologs also play roles in neuronal function and may be factors in the pathogenesis of human neurological disease.…”
Section: Rbms1/2/3 Are Candidates For Nervous System Function In Humansmentioning
confidence: 75%
“…The gene expression data used in this study were downloaded from the Gene Expression Omnibus (GEO) repository (accession numbers GDS 810 and GDS4136, http://www.ncbi.nlm.nih.gov) [32,33]. The GDS810 (31 samples) were detected using the Gene expression array (Affymetrix Human Genome U133A Array).…”
Section: Gene Expression Testmentioning
confidence: 99%